Exotic plants accumulate and share herbivores yet dominate communities via rapid growth - Allen, Warwick J.; Waller, Lauren P.; Barratt, Barbara I. P.; Dickie, Ian A.; Tylianakis, Jason M. (Nature communications, 2021)
Herbivores may facilitate or impede exotic plant invasion, depending on their direct and indirect interactions with exotic plants relative to co-occurring natives. However, previous studies investigating direct effects have mostly used pairwise native-exotic comparisons with few enemies, reached conflicting conclusions, and largely overlooked indirect interactions such as apparent competition. Here, we ask whether native and exotic plants differ in their interactions with invertebrate herbivores. We manipulate and measure plant-herbivore and plant-soil biota interactions in 160 experimental mesocosm communities to test several invasion hypotheses. We find that compared with natives, exotic plants support higher herbivore diversity and biomass, and experience larger proportional biomass reductions from herbivory, regardless of whether specialist soil biota are present. Yet, exotics consistently dominate community biomass, likely due to their fast growth rates rather than strong potential to exert apparent competition on neighbors. We conclude that polyphagous invertebrate herbivores are unlikely to play significant direct or indirect roles in mediating plant invasions, especially for fast-growing exotic plants. It is unclear whether plant-herbivore interactions systematically favour exotic plant species. Here the authors investigate plant-herbivore and plant-soil biota interactions in experimental mesocosm communities, finding that exotic plants dominate community biomass despite accumulating more invertebrate herbivores.